1992
DOI: 10.1007/bf01296003
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of gastric mucosal injury following ischemia and reperfusion

Abstract: The mechanisms of gastric mucosal injury following a period of ischemia remain unclear. The aim of this study was to determine the relative contributions of ischemia, reperfusion, and reactive oxygen metabolites to mucosal injury induced by temporary occlusion of the celiac artery. Rats were subjected to 30 min of gastric ischemia in the presence of 100 mM HCl. Reperfusion periods ranged from 1 min to 24 hr. Drug treatments included allopurinol (100 mg/kg) or a combination of superoxide dismutase (15,000 units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Allopurinol, administered by acute pretreatment by the intraperitoneal route, or following oral administration over 2 days, reduced the mucosal injury induced by local infusion nitroprusside or SNAP. As with the protective actions of allopurinol on gastric mucosal injury following hypovolaemic shock in the gastric mucosa and ischaemia reperfusion in the stomach and intestine (Granger et al, 1981;Itoh & Guth, 1985;Perry et al, 1986;Andrews et al, 1992), such actions should reflect the inhibition of xanthine oxidase. The specificity of these actions of allopurinol in the present study was demonstrated by its failure to attenuate the mucosal injury induced by close-arterial infusion of endothelin-1.…”
Section: Effects Of Anti-neutrophil Serummentioning
confidence: 99%
“…Allopurinol, administered by acute pretreatment by the intraperitoneal route, or following oral administration over 2 days, reduced the mucosal injury induced by local infusion nitroprusside or SNAP. As with the protective actions of allopurinol on gastric mucosal injury following hypovolaemic shock in the gastric mucosa and ischaemia reperfusion in the stomach and intestine (Granger et al, 1981;Itoh & Guth, 1985;Perry et al, 1986;Andrews et al, 1992), such actions should reflect the inhibition of xanthine oxidase. The specificity of these actions of allopurinol in the present study was demonstrated by its failure to attenuate the mucosal injury induced by close-arterial infusion of endothelin-1.…”
Section: Effects Of Anti-neutrophil Serummentioning
confidence: 99%
“…NO synthesis modulators (L-arginine, 200 mg/kg or L-NAME, 10 mg/kg or L-NAME with L-arginine) were injected intraperitoneally to the rats. The doses of NO synthesis modulators were adapted from previous studies dealing with gastroprotection against necrotizing agents in rats [5,24]. Control animals received an equivalent volume of saline.…”
Section: Animal Preparationmentioning
confidence: 99%
“…More and more evidence suggests that the majority of injuries occur during reperfusion [3][4][5], and this may be attributable to reactive oxygen metabolites initially generated at the level of the vasculature [6]. Sources of reactive oxygen metabolites in reperfusing tissues include the xanthine oxidase system, which produces superoxides and hydrogen peroxides during reperfusion [7,8], and activated neutrophils, which infiltrate into the tissues and bind to the microvascular endothelium [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet activating factor (12,13), acidosis (14) and free radicals (15,16) have been reported to participate in mucosal injury induced by ischemia reperfusion (I/R). In our previous study, complement activation played an essential role in systemic shock following intestinal I/R (17).…”
mentioning
confidence: 99%